Political Actors and the Challenges of Peacebuilding in Cote d’Ivoire - Agunbiade, Doyinsola; Abiodun, Temitope Francis (Advances in Social Sciences Research Journal, 2025)
This paper seeks to interrogate the origin of the Ivorian conflict as characterized by several political actors at different times and challenges of peacebuilding inherent in the history of the country. The quest and tussle for power, issues of identity, rights over land ownership, ethnicity, and military incursion into politics amidst others formed the bane and basis of the Ivorian conflict. Scholarly works have largely focused attention to an array of conflicts in Cote D’Ivoire with little attention given to the classification of political actors involved, and the context of challenges of peace-building in the conflict situations. The study explored the political actors, and how they have contributed to the conflict as well as the challenges of peace-building in Cote d’Ivoire. Paul Lederach’s Conflict Transformation Theory served as the framework while the descriptive design was adopted for the study. Primarily, content analysis as a method of data analysis was used in analyzing data collected for the purpose of this study. This was premised on the source of data which relied majorly but not limited to written text, interviews and online sources. The study identified both internal and external political actors and as well explored activities towards peacebuilding and the challenges of peace-building within the Ivorian conflicts. The study, therefore, concluded and recommended that, stemming the tide of future relapse into violent conflict in Cote d’Ivoire, it is imperative to have a self-sustaining and peacebuilding process in the country.